2019
DOI: 10.2106/jbjs.19.00146
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet Use Does Not Affect Functional Outcomes or Pain After Total Knee Arthroplasty

Abstract: Background: The use of a tourniquet during total knee arthroplasty (TKA) is controversial. Pain and return to function are believed, by some, to be influenced by the use of a tourniquet. The hypothesis of this study was that use of a tourniquet would delay postoperative functional recovery and increase pain as compared with no tourniquet use. Methods: Two hundred patients were recruited for this prospective, double-blinded, randomized controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 25 publications
12
62
1
Order By: Relevance
“…Functional results similar to ours have been reported by Goel et al and McCarthy et al who showed that there is no differences in pain, ROM and quadriceps function at any point during the in-hospital period between tourniquet and tourniquet-less surgery [9,20]. By contrast, Huang et al reported that tourniquet use was associated with lower ROM and higher pain up until the 5th postoperative day [21].…”
Section: Study Aimssupporting
confidence: 89%
See 1 more Smart Citation
“…Functional results similar to ours have been reported by Goel et al and McCarthy et al who showed that there is no differences in pain, ROM and quadriceps function at any point during the in-hospital period between tourniquet and tourniquet-less surgery [9,20]. By contrast, Huang et al reported that tourniquet use was associated with lower ROM and higher pain up until the 5th postoperative day [21].…”
Section: Study Aimssupporting
confidence: 89%
“…There is conflicting evidence regarding pain, functional outcome, blood loss from heterogeneous samples of tourniquet use [3][4][5][6][7][8]. Advocates of tourniquet use cite better visualisation of the surgical field, better cement interdigitation, and overall less blood loss [9][10][11]. Conversely, tourniquet use might relate to increased pain, limb ischaemia, delayed range of motion (ROM) and quadriceps function recovery, accelerated quadriceps sarcopenia in the elderly, more thromboembolic events, increased length of stay (LOS), and a higher hospital readmission rate [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcomes of the study were surgical field visualization including surgeon-rated difficulty in visualization and number of surgical field clearances [17,18]. Surgeon-rated difficulty in visualization prior to using epinephrine in Epinephrine group and before cementing in two groups, was graded (Grading scale for difficulty of intraoperative visualization due to blood: 0 No Difficulty; 1 Some difficulty, but did not affect the case; 2 Moderate difficulty; 3 Severe difficulty), and independently assessed by two senior authors (Z. L. and W. G.) at the end of the surgery; Number of surgical field clearances (excluding action of using epinephrine-soaked gauzes) was counted by another author (H. L.) in two groups over the period from the finish of bone cutting through the cement hardening.…”
Section: Outcome Measurementmentioning
confidence: 99%
“…Tourniquet use in TKA is common and has been demonstrated to decrease intraoperative blood loss and allow for increased surgical field visualization [8,9]. When compared to TKA where no tourniquet is used, current literature has shown functional and pain outcomes to be similar [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Tourniquet use in TKA is common and has been demonstrated to decrease intraoperative blood loss and allow for increased surgical field visualization [8,9]. When compared to TKA where no tourniquet is used, current literature has shown functional and pain outcomes to be similar [8,10]. Dennis et al [11] echoed these findings in a randomized prospective trial, adding that there is an early (<3 months) quadriceps strength advantage in tourniquetless TKA with unknown clinical significance.…”
Section: Introductionmentioning
confidence: 99%